Assessment of building failure within and around quarries (2019)
The substructures of various engineering structures that were erected on the earth are being were been supported by the soil. Hence, the nature of the soil supporting these structures becomes an important issue. Quarry blasting peak particle velocity (QBPPV) is not sufficient to ascertain the causes of foundation failure, therefore, the physical parameters governing the competency of the soil supporting engineering structures need to be determine. This work investigated the possible causes of foundation failure of buildings within the vicinity of quarries. The investigation was done by carrying out Vertical Electrical Sounding (VES) and Radial Vertical Electrical Sounding (RVES) using Campus omega terrameter. The results show that buildings found within this area have shallow foundation and their foundations founded on sandy clay which can still support foundation The values of the degree of fracturing was found not to exceed 1.53 in this region which was not the case with the previous radial vertical electrical soundings, 1.94 was calculated as the highest degree of fracturing for RVES 1 while 1.83 was calculated for RVES 2. In all the RVES, degree of fracturing ranges between 1.02 to 1.94.